2020
DOI: 10.1002/agj2.20342
|View full text |Cite
|
Sign up to set email alerts
|

Irrigated soybean response to granular fertilizer potassium application timing

Abstract: Amelioration of K deficiency during the growing season requires knowledge of critical tissue concentrations and crop yield response to fertilization time. Our objectives were to characterize the yield and uptake responses of K-deficient irrigated soybean [Glycine max (L.) Merr.] to in-season fertilizer-K application time and rate, evaluate fertilizer-potassium-recovery efficiency (FKRE), and evaluate how leaflet-K concentration responds to K-fertilization time. Six trials were established on silt loam soils. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…Slaton et al (2020) reported that yields of K-deficient soybean may be increased by the application of fertilizer-K into the R5 development stage. Slaton et al (2020) reported no soybean yield loss when hidden hunger K deficiency was corrected before 44 DAR1, but more severe deficiency required earlier action to prevent yield loss associated with K deficiency. The petiole-K and trifoliolate leaf-K concentrations associated with 85 and 75% relative yields were also predicted across time to provide estimates of the degree of deficiency (Figures 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Slaton et al (2020) reported that yields of K-deficient soybean may be increased by the application of fertilizer-K into the R5 development stage. Slaton et al (2020) reported no soybean yield loss when hidden hunger K deficiency was corrected before 44 DAR1, but more severe deficiency required earlier action to prevent yield loss associated with K deficiency. The petiole-K and trifoliolate leaf-K concentrations associated with 85 and 75% relative yields were also predicted across time to provide estimates of the degree of deficiency (Figures 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…Parvej et al (2016) also reported lower correlations between tissue-K concentrations during early and late reproductive development stages and soybean relative yield. The weak correlation during the late vegetative and early reproductive growth of indeterminate soybean is attributed to the fact that flowering begins before plant shoots and roots are fully developed (Mitchell & Russell, 1971), rapid dry matter accumulation and nutrient uptake during subsequent growth may influence tissue nutrient concentrations (Bender et al, 2015), and K-deficiency may be effectively ameliorated through early to mid-reproductive development (Slaton et al, 2020). Although the tissue-K concentrations during early reproductive growth may be informational, tissue concentrations from samples collected beginning at the R2 stage or >15 DAR1 will most accurately characterize the plant-K nutritional status for management decisions regarding the need for additional fertilizer-K application.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…show symptoms of chlorosis beginning on the margins of the leaves, with yield loss caused by reductions in pods plant −1 , seed pod −1 , and seed weight along with increased seed abortion (Parvej, Slaton, Purcell, & Roberts, 2015, 2016). The severity of the deficiency dictates when and where on the plant the symptoms appear (Slaton, Roberts, Ross, & Richmond, 2020). Soybean can become more susceptible to plant diseases when K nutrition is low, such as seed decay caused by Diaporthe/Phompsis spp.…”
Section: Introductionmentioning
confidence: 99%